Evaluation of Female Infertility by Laparoscopy in a Secondary Level Infertility Care Centre (Journal of Shaheed Suhrawardy Medical College, 2019)
Introduction: infertility is regarded as an upsetting and difficult life experience for some women with elevated levels of anxiety & depression. Laparoscopy is the gold standard in diagnosing various aspects of female subfertility as well as treatment of some of them at the same time.Secondary level infertility care centre includes all those can manage every aspects of problems of infertily except IVF-ET and other advance aspects of management.Objective: To find out the role of laparoscopy in the management of infertile women in a secondary level infertility care centre.Study Design: Prospective cross sectional study.Setting: Fertility care centre, Department of Obst. &Gynaecology Dhaka Medical College Hospital from January 2018 to June 2018.Methods: During the study period 328 infertile women attended infertility outdoor. .Among them 48 were admitted for diagnostic laparoscopy.Results: Out of forty eight women 26 (54%) had primary infertility, 22 (46%) had secondary infertility.The findings were PCOS in 22% of cases, endometriosis in 14%, PID in 15% cases,unexplained in 20%, fibroid uterus in 6% cases congenital anomaly of uterus in 1% and others in 22% .Conclusion: Laparoscopy is the gold standard in evaluating infertile women.Some women would have a correctable problem found at laparoscopy that would not be discovered with any other fertility screening tests like endometriosis.J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 9-12